Respostas
respondido por:
0
fazendo
(A+B)
1+0=1
2+-2=0
0+1=1
1+1=2
1 0
1 2
ou seja
a11=1
a12=0
a21=1
a22=2
São os elementos de (A+B)
agora (A+B)C
1×1+0×-1=1
1×0+0×2=0
1×1+2×-1=1+-2=-1
1×0+2×2=4
a matriz de (A+B)C
1 0
-1 4
ou seja
b11=1
b12=0
b21=-1
b22=4
espero ter ajudado
(A+B)
1+0=1
2+-2=0
0+1=1
1+1=2
1 0
1 2
ou seja
a11=1
a12=0
a21=1
a22=2
São os elementos de (A+B)
agora (A+B)C
1×1+0×-1=1
1×0+0×2=0
1×1+2×-1=1+-2=-1
1×0+2×2=4
a matriz de (A+B)C
1 0
-1 4
ou seja
b11=1
b12=0
b21=-1
b22=4
espero ter ajudado
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás